Romane paramiša - Romani fairy tales - Červeňáková-Laliková, Helena (Romano džaniben, 2020)
A selection of original texts based on folk tales, anecdotes, and other stories passed down among the Roma people of northern Gemer. The texts were first published by the author on her Facebook profile Romane paramiša (Roma Fairy Tales). Within this issue, they also serve as an example of the northern Gemer dialect of Romani, whose phonological specifics are discussed in the reviewed section.